Imidacloprid Biodegradation by Soil Bacteria and Relationship to Soil Bacterial Diversity - Moghaddam, Nasrin Sabour (2011)
Imidacloprid, [1-(6-chloro-3-pyridylmethyl)-N-nitroimidazolidin- 2-ylideneamine], is a second generation neonicotinoid pesticide (chloronicotinyl insecticide) that is used to treat plants against threatening pests. Application of imidacloprid as plant, seed and soil treatments has become a common practice to control pests on rice, maize, potatoes and vegetables. Besides controlling the pests in plants and soil, imidacloprid have come into direct or indirect contact to the nontargeted soil microorganisms and may affect their population and activity of microbial communities in soil. Although the use of imidacloprid has been gaining popularity in agricultural and residential settings, the factors leading to its dissipation in soil are not clearly understood. Field dissipation rates of imidacloprid are widely variable, and it has been reported as a stable compound in the environment with half live exceeding 180 days in non-vegetated soil and more than three years in dry and aerobic conditions. Whilst possible microbial metabolites of imidacloprid have been reported in soil metabolism studies, direct evidence of imidacloprid biodegradation and its effects on the genomic diversity of bacteria has not been fully evaluated especially in tropical area. The objectives of this research were the isolation and identification of imidacloprid degrading bacteria from soil samples in laboratory condition, and to determine effects of imidacloprid on the diversity of soil bacteria using suitable molecular markers. Several extraction methods have been published for determination of imidacloprid residues in different matrixes, but there is no record of Soxhlet extraction for imidacloprid residue analysis and comparison of its efficiency with other extraction methods. Therefore we also optimized reliable extraction method with appropriate use of organic solvent, to quantify the concentration of imidacloprid present in the sandy clay loam soil, with applying Soxhlet and liquid extraction method using HPLC. A comparison of the Soxhlet and liquid extraction methods for the sandy loamy clay soil indicated that, the two applied extraction methods performed equally well for the imidacloprid detection in terms of recovery percentage for lower concentration (1 mg kg-1), but efficiency of liquid extraction over Soxhlet in higher concentrations (5 & 10 mg kg-1) was confirmed. Using standard Mineral Salt Medium (MSM), Nutrient Broth (NB) and Tryptic Soy Broth (TSB) media for different collected soils, a total of 120 different bacteria strains were isolated and biodegradative ability of all isolates were tested on N limited and C limited media. As a result five bacteria were confirmed to be capable for degradation of imidacloprid in C limited media, which were identified as Pseudomonas putida, Bacillus sp., B. subtilis, Brevibacterium sp. and Rhizobium sp. using 16S rRNA sequencing. ERIC-PCR and RAPD-PCR were used to determine the influence of imidacloprid on soil bacterial diversity. The results showed that the long-term application of imidacloprid has different impacts on bacterial populations, and the numbers of viable Gram negative bacteria in soil can be reduced due to pesticides uses and Gram-positive bacteria gradually became dominant in the soils that had been treated by imidacloprid. The cluster analysis clearly showed that soil bacterial diversity has been changed in response to imidacloprid.